2011
DOI: 10.1073/pnas.1111262109
|View full text |Cite
|
Sign up to set email alerts
|

Genome and physiology of a model Epsilonproteobacterium responsible for sulfide detoxification in marine oxygen depletion zones

Abstract: Eutrophication and global climate change lead to expansion of hypoxia in the ocean, often accompanied by the production of hydrogen sulfide, which is toxic to higher organisms. Chemoautotrophic bacteria are thought to buffer against increased sulfide concentrations by oxidizing hydrogen sulfide before its diffusion to oxygenated surface waters. Model organisms from such environments have not been readily available, which has contributed to a poor understanding of these microbes. We present here a detailed stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
237
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 136 publications
(245 citation statements)
references
References 47 publications
5
237
1
Order By: Relevance
“…Weerakoon and Olson (2008) also showed that this unusual mechanism is due to differences in the NuoE/F subunits that interact with NADH in canonical complex I. Interestingly, they note that S. denitrificans and other autotrophic Epsilonproteobacteria also possess non-canonical NuoEF subunits. So far, this different NuoEF composition has also been observed in all genomes of Sulfurimonas and Sulfurovum sequenced to date (Nakagawa et al, 2007;Sievert et al, 2008;Sikorski et al, 2010;Grote et al, 2012;Cai et al, 2014)…”
Section: Reverse Electron Transportmentioning
confidence: 99%
See 1 more Smart Citation
“…Weerakoon and Olson (2008) also showed that this unusual mechanism is due to differences in the NuoE/F subunits that interact with NADH in canonical complex I. Interestingly, they note that S. denitrificans and other autotrophic Epsilonproteobacteria also possess non-canonical NuoEF subunits. So far, this different NuoEF composition has also been observed in all genomes of Sulfurimonas and Sulfurovum sequenced to date (Nakagawa et al, 2007;Sievert et al, 2008;Sikorski et al, 2010;Grote et al, 2012;Cai et al, 2014)…”
Section: Reverse Electron Transportmentioning
confidence: 99%
“…In contrast to the Nautiliales, nearly all Campylobacterales isolates reported thus far have the potential to use oxygen, and in some cases tolerate levels approaching atmospheric concentrations Takai et al, 2006). Even for those reported to be strict anaerobes, genome sequences contain a cbb 3 -type high-affinity cytochrome c oxidase (Grote et al, 2012;Cai et al, 2014), suggesting the ability to use oxygen as an electron acceptor is typical of autotrophic Campylobacterales. The use of nitrate and sulfur as electron acceptors is also common in this lineage but obligate aerobes do exist .…”
Section: 3mentioning
confidence: 99%
“…NBC37-1; Inagaki et al, 2004) and Nitratifractor (i.e., Nitratifractor Salsuginis Nakagawa et al, 2005b). Additionally, Sievert et al (2008) and Grote et al (2012) reported that other ε-proteobacteria of the genus Sulfurimonas (Sulfurimonas denitrificans str. DMS1251 and Sulfurimonas gotlandica str.…”
Section: Denitrifier Community In the Subsurface Biospherementioning
confidence: 99%
“…Nitrogen is an essential macronutrient for all organisms, and oceanic N sinks that remove biologically available N via denitrification and anaerobic ammonium (NH N 2 gas, is mediated by both heterotrophic and autotrophic bacteria and occurs in the anoxic and suboxic oceanic water-column (Codispoti et al, 2001;Lavik et al, 2009;Ward et al, 2009;Grote et al, 2012) and sediments (e.g., Christensen et al, 1987). For the past decade, anammox, i.e., the conversion of NH + 4 and nitrite (NO − 2 ) to N 2 gas by autotrophic anaerobic bacteria, has also been reported to account for a significant part of the N loss in oceanic anoxic zones (Dalsgaard et al, 2003;Kuypers et al, 2003;2005;Lam et al, 2009;Jensen et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Many are chemolithotrophs [11] that obtain energy by oxidizing compounds found in 32 their environment. The Sulfurospirillum, Sulfurimonas,Sulfuricurvum,Thiovulum,and some Arcobactergenera 33 from the Campylobacteralesorder are environmental bacteria [12,13], with habitats ranging from marine 34 hydrothermal vents and coastal sediments [14], underground oil-storage facilities [15], plant roots in salt 35 marsh sediments [16] and pond mud [17]. Intriguingly, there are multiple cases of epsilon-proteobacteria that 36 combine animal association with hydrothermal vent environments by establishing symbioses with gastropods 37 and annelids endemic to vents [18,19].…”
mentioning
confidence: 99%